Wear-corrosion-resistant and toughness-integrated multi-process coupling high-entropy alloy bionic structure coating and preparation method thereof

Through multi-process coupling technology, a high-entropy alloy bionic structure coating of wear resistance-strong and tough integration solves the problem of strong toughness and corrosion resistance in extreme environments in extreme environments. promote.

CN119332238APending Publication Date: 2025-01-21HARBIN ENG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411452415.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

High-entropy alloys are difficult to improve their toughness and corrosion resistance at the same time in extreme environments.

Method used

Adopt multi -process coupling technology, form a high -entropy alloy film on the surface of the substrate material through the laser melting process on the surface of the substrate material, and to form a high -entropy alloy film through ultrasonic deep roll treatment and electrochemical sedimentation process to form wear -resistant resistance Eclipse-strong integrated multi-process coupling high-entropy alloy bionic structure coating.

Benefits of technology

It significantly improves the overall hardness, fatigue resistance, wear resistance and abrasion and corrosion resistance of the coating, and meet the application requirements in extreme environments such as high temperature, strong impact, and strong corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332238A_ABST
    Figure CN119332238A_ABST
Patent Text Reader

Abstract

The invention discloses a wear-corrosion-resistant and toughness-integrated multi-process coupling high-entropy alloy bionic structure coating and a preparation method thereof, and aims to solve the problems that the toughness of a high-entropy alloy is difficult to synergistically improve and the corrosion resistance is insufficient. In the high-entropy alloy bionic structure coating, Al < x > FeCoCrNiy eutectic high-entropy alloy powder serves as cladding powder, a laser cladding process is adopted for preparing an eutectic high-entropy alloy coating on the surface of a base material, FeCoCrNiX high-entropy metal ceramic powder serves as cladding powder, and a high-entropy metal ceramic layer is formed on the eutectic high-entropy alloy coating in a cladding mode through the laser cladding process. And then ultrasonic deep rolling treatment is carried out, and a high-entropy alloy film is deposited on the composite coating. Based on the shell-shaped biological structure, the high-strength-and-toughness eutectic high-entropy alloy layer with the two phases serves as a transition layer to connect the base body and the high-entropy metal ceramic layer, the high-entropy alloy composite coating of the structure with the strong outer portion and the tough inner portion is formed, the overall wear-resisting and friction-reducing performance of the coating is improved, and the corrosion resistance of the surface of the coating is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of surface engineering, and in particular relates to a multi-process coupled high-entropy alloy bionic structure coating integrating wear resistance and toughness and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, especially in high-tech fields such as aerospace, national defense, and nuclear energy, more stringent requirements have been placed on the performance of materials. Traditional alloy materials often cannot meet these strict application requirements under extreme environments such as high temperature, strong impact, and strong corrosion. With the introduction of the concept of high entropy alloys, a new path has been opened up for alloy design.

[0003] In nature, shell-like organisms are a typical multi-layer structure, each layer has different materials and functions, and the synergistic effect enhances the overall strength and toughness, and the shell film on its surface provides it with excellent high durability and corrosion resistance. For example, inspired by the shell structure, some researchers are currently designing high-strength and toughness composite materials on this basis. The "Fe-Cu-HEA high-strength and toughness bionic composite material based on shell structure and its preparation method" proposed by Taiyuan University of Technology has designed a steel plate layer as the first layer, a copper plate layer as the second layer, and an AlCoCrFeNi high-entropy alloy layer with an equiatomic ratio from bottom to top, but the overall hardness of the material is uneven and cannot meet the needs of practical applications. In addition, the "A laser additive manufacturing method for alloys imitating shell structure" proposed by Nanjing Liankong Intelligent Additive Research Institute Co., Ltd. melts multiple layers of high-entropy alloy layers on a titanium alloy substrate, but the method has complex steps and only improves the strength and plastic toughness of the material, and the actual application occasion is single. Therefore, the method of combining high-entropy alloys with shell-like biological structures to design materials with multiple properties has broad application prospects. Summary of the invention

[0004] The present invention aims to solve the problem that the strength and toughness of high entropy alloys are difficult to improve synergistically and the corrosion resistance is insufficient, and to provide a multi-process coupled high entropy alloy bionic structure coating with integrated wear resistance and toughness and a preparation method thereof.

[0005] The wear-resistant and tough multi-process coupled high-entropy alloy bionic structure coating of the present invention is composed of a eutectic high-entropy alloy coating, a high-entropy metal ceramic layer and a high-entropy alloy film. x FeCoCrNi yEutectic high entropy alloy powder is used as cladding powder, and a eutectic high entropy alloy coating is prepared on the surface of a substrate by a laser cladding process. Then, FeCoCrNiX high entropy metal ceramic powder is used as cladding powder, and a high entropy metal ceramic layer is formed on the eutectic high entropy alloy coating by a laser cladding process. The eutectic high entropy alloy coating and the high entropy metal ceramic layer form a composite coating. The composite coating is subjected to ultrasonic deep rolling treatment, and a high entropy alloy film is deposited on the composite coating by an electrochemical deposition process, thereby obtaining a multi-process coupled high entropy alloy bionic structure coating.

[0006] The X in the FeCoCrNiX high entropy metal ceramic powder represents ceramic particles; the electrolyte in the electrochemical deposition process includes at least four metal salts of soluble aluminum salt, cobalt salt, chromium salt, iron salt, nickel salt, manganese salt, copper salt, and titanium salt, a complexing agent, and a reducing agent.

[0007] The preparation method of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structure coating of the present invention is achieved by the following steps:

[0008] 1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material;

[0009] 2. Preparation of Al x FeCoCrNi y Eutectic high entropy alloy powder:

[0010] Al powder, Fe powder, Co powder, Cr powder and Ni powder were mixed in a ball mill according to the atomic ratio of Al:Fe:Co:Cr:Ni=x:1:1:1:y to obtain Al x FeCoCrNi y Eutectic high entropy alloy powder;

[0011] 3. Preparation of FeCoCrNiX high entropy metal ceramic powder, X represents ceramic particles:

[0012] Fe powder, Co powder, Cr powder, Ni powder and ceramic particles X are mixed in a ball mill according to a mass ratio of Fe:Co:Cr:Ni:X=1:1:1:1:1 to obtain FeCoCrNiX high entropy metal ceramic powder;

[0013] 4. Al x FeCoCrNi y Eutectic high entropy alloy powder is used as cladding powder, and a eutectic high entropy alloy coating is prepared on the surface of the substrate by laser cladding process;

[0014] 5. Using FeCoCrNiX high entropy metal ceramic powder as cladding powder, a laser cladding process is used to in-situ clad the eutectic high entropy alloy coating to form a high entropy metal ceramic layer, thereby obtaining a substrate material with a composite coating;

[0015] 6. Grind and clean the base material with the composite coating in turn;

[0016] 7. Perform ultrasonic deep rolling treatment on the composite coating on the base material;

[0017] 8. Using an electrochemical deposition process, a high entropy alloy film is deposited on the composite coating to obtain a multi-process coupled high entropy alloy bionic structure coating;

[0018] The electrolyte in the electrochemical deposition process in step eight includes at least four metal salts of soluble aluminum salt, cobalt salt, chromium salt, iron salt, nickel salt, manganese salt, copper salt and titanium salt, a complexing agent and a reducing agent.

[0019] The present invention adopts laser cladding technology to connect the substrate and the high entropy metal ceramic layer with a dual-phase high-strength and tough eutectic high-entropy alloy layer as a transition layer on the surface of the substrate material, so as to form a high-entropy alloy composite coating with a strong outer and tough inner structure. Residual stress is introduced into the surface of the composite coating by ultrasonic deep rolling and the surface is ultrasonically nano-surface modified, so that the surface grains of the composite coating are refined, the surface roughness is reduced, and the overall hardness and fatigue resistance of the composite coating are improved. Finally, a high entropy alloy film is formed on the surface of the composite coating by electrochemical deposition, so that the overall wear resistance and friction reduction performance of the coating is improved while the coating has good surface corrosion resistance.

[0020] The design and preparation method of the multi-process coupling high entropy alloy bionic structure coating with integrated wear resistance and toughness of the present invention, wherein Al x FeCoCrNi y The eutectic transition layer is a high-strength and tough dual-phase structure with the advantages of high strength and good toughness. The intermediate FeCoCrNiX high-entropy metal ceramic coating improves the impact resistance of the overall composite coating, and the surface grains of the coating after ultrasonic deep rolling are refined, which greatly increases the overall hardness and fatigue resistance of the coating. The top high-entropy alloy film increases the wear resistance and friction reduction of the overall composite coating while giving it good corrosion resistance. The overall shell-like biological structure of the composite coating is combined with high-entropy alloys and multi-process processing technology to design a high-strength, tough and wear-resistant composite coating, which provides a new idea and method for the design and development of bionic structural coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The structural schematic diagram of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating of the present invention; Figure numbers: 1-base material; 2-eutectic high-entropy alloy coating; 3-high-entropy metal ceramic coating; 4-high-entropy alloy film; 5-ceramic hard phase;

[0022] Figure 2 Schematic diagram of longitudinal and transverse directions of ultrasonic deep rolling treatment in the embodiment;

[0023] Figure 3 The cross-sectional microhardness diagram of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structure coating obtained in the embodiment;

[0024] Figure 4 The friction coefficient curve of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structure coating obtained in the example;

[0025] Figure 5 This is the polarization curve of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structure coating obtained in the example. DETAILED DESCRIPTION

[0026] Specific implementation method 1: The preparation method of the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structure coating in this implementation method is implemented according to the following steps:

[0027] 1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material;

[0028] 2. Preparation of Al x FeCoCrNi y Eutectic high entropy alloy powder:

[0029] Al powder, Fe powder, Co powder, Cr powder and Ni powder were mixed in a ball mill according to the atomic ratio of Al:Fe:Co:Cr:Ni=x:1:1:1:y to obtain Al x FeCoCrNi y Eutectic high entropy alloy powder;

[0030] 3. Preparation of FeCoCrNiX high entropy metal ceramic powder, X represents ceramic particles:

[0031] Fe powder, Co powder, Cr powder, Ni powder and ceramic particles X are mixed in a ball mill according to a mass ratio of Fe:Co:Cr:Ni:X=1:1:1:1:1 to obtain FeCoCrNiX high entropy metal ceramic powder;

[0032] 4. Al x FeCoCrNi y Eutectic high entropy alloy powder is used as cladding powder, and a eutectic high entropy alloy coating is prepared on the surface of the substrate by laser cladding process;

[0033] 5. Using FeCoCrNiX high entropy metal ceramic powder as cladding powder, a laser cladding process is used to in-situ clad the eutectic high entropy alloy coating to form a high entropy metal ceramic layer, thereby obtaining a substrate material with a composite coating;

[0034] 6. Grind and clean the base material with the composite coating in turn;

[0035] 7. Perform ultrasonic deep rolling treatment on the composite coating on the base material;

[0036] 8. Using an electrochemical deposition process, a high entropy alloy film is deposited on the composite coating to obtain a multi-process coupled high entropy alloy bionic structure coating;

[0037] The electrolyte in the electrochemical deposition process in step eight includes at least four metal salts of soluble aluminum salt, cobalt salt, chromium salt, iron salt, nickel salt, manganese salt, copper salt and titanium salt, a complexing agent and a reducing agent.

[0038] In this embodiment, the bionic structure self-lubricating and wear-resistant high-entropy alloy composite coating composed of the eutectic transition layer and the high-entropy metal ceramic includes Al x FeCoCrNi y The eutectic high entropy toughness transition layer, the FeCoCrNiX high entropy metal ceramic intermediate layer and the high entropy alloy film top layer are clad on the surface of the base material by laser cladding process. x FeCoCrNi y A eutectic high entropy toughness transition layer is formed, and then a FeCoCrNiX high entropy metal ceramic layer is continuously clad on the surface of the eutectic high entropy transition layer, wherein X is one of WC, TiC, Cr3C2, and SiC, and the composite coating is subjected to ultrasonic deep rolling treatment and then an electrochemical deposition process is used to form a high entropy alloy film on the surface of the composite coating.

[0039] This embodiment provides a design and preparation method for a multi-process coupled high-entropy alloy bionic structural coating with integrated wear resistance and toughness. Based on the shell-like biological structure, a composite coating with a wear-resistant and corrosion-resistant high-entropy alloy film as the outer layer, a high-strength high-entropy metal ceramic layer as the middle layer, and a high-strength and toughness dual-phase eutectic high-entropy alloy as the transition layer is successfully prepared. Compared with a single eutectic high-entropy alloy coating, the addition of a high-entropy metal ceramic coating improves the overall strength and impact resistance of the composite coating, and the high-entropy alloy film improves the wear resistance and wear reduction of the composite coating, while enhancing the corrosion resistance of the coating, greatly improving the comprehensive performance of the composite coating.

[0040] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that the base material described in step 1 is 38CrMoAl high-strength steel.

[0041] Specific implementation method three: This implementation method is different from specific implementation method one or two in that Al in step two x FeCoCrNi y The preparation method of eutectic high entropy alloy powder is as follows:

[0042] According to the atomic ratio of Al:Fe:Co:Cr:Ni=x:1:1:1:y, the metal powders were mixed in a ball mill. The ball-to-material mass ratio was controlled to be 2:1. The rotation speed was 300-350r / min. The ball milling time was 40-60min. Al was obtained after drying. x FeCoCrNi y Eutectic high entropy alloy powder;

[0043] The Al x FeCoCrNi y In eutectic high entropy alloys, x is 0.7 to 1 and y is 1 to 2.1.

[0044] Specific implementation method 4: This implementation method is different from any one of specific implementation methods 1 to 3 in that the ceramic particles in step 3 are WC, TiC, Cr3C2 or SiC.

[0045] Specific implementation method five: This implementation method is different from specific implementation methods one to four in that in the laser cladding process in step four, the laser wavelength is controlled to be 1053 nm, the laser power is 1500-2000 W, and the scanning rate is 10-20 mm / s.

[0046] Specific implementation method 6: This implementation method is different from specific implementation methods 1 to 5 in that in the laser cladding process in step 5, the laser wavelength is controlled to be 1053nm, the laser power is 1500-2500w, and the scanning rate is 8-15mm / s.

[0047] Specific embodiment seven: The difference between this embodiment and any one of specific embodiments one to six is ​​that the process parameters for controlling the ultrasonic deep rolling treatment in step seven are: ultrasonic vibration frequency of 20 to 30 kHz, ultrasonic deep rolling times of 5 to 15 times, longitudinal feed speed of 20 to 30 mm / min, transverse feed step of 0.1 to 0.3 mm, and applied force of 250 to 300 N.

[0048] Specific implementation eight: This implementation differs from any one of specific implementations one to seven in that the complexing agent in the electrolyte in step eight is citric acid or trisodium citrate, and the reducing agent is sodium phosphite or ascorbic acid.

[0049] Specific embodiment nine: The difference between this embodiment and any one of specific embodiments one to eight is that in the electrochemical deposition process in step eight, a graphite rod is used as the anode, a substrate material with a composite coating is used as the cathode, the electrolyte temperature is 30 to 80°C, and a constant potential of 0.5 to 3V is used for electroplating deposition for 5 to 10 minutes.

[0050] Specific embodiment ten: This embodiment differs from specific embodiments one to nine in that the thickness of the eutectic high entropy alloy coating is 0.3 to 0.6 mm, and the thickness of the high entropy metal ceramic layer is 0.3 to 0.5 mm.

[0051] Embodiment: The preparation method of the multi-process coupled high entropy alloy bionic structure coating with integrated wear resistance and toughness in this embodiment is implemented according to the following steps:

[0052] 1. Grinding, polishing and cleaning the 38CrMoAl high-strength steel matrix material in sequence to obtain a pretreated matrix material;

[0053] 2. Preparation of AlFeCoCrNi 2.1 The method of eutectic high entropy alloy powder is as follows:

[0054] The metal powders were mixed in a planetary ball mill according to the atomic ratio of Al:Fe:Co:Cr:Ni=1:1:1:1:2.1. The ball milling medium was Al2O3 ceramic balls. The ball-to-material mass ratio was 2:1. The rotation speed was 300r / min. The ball milling time was 60min. After the milling, it was dried at 120℃ for 2h to obtain AlFeCoCrNi 2.1 High entropy alloy powder;

[0055] 3. The method for preparing FeCoCrNiX high entropy metal ceramic powder is as follows:

[0056] The metal powders and ceramic powders were mixed in a planetary ball mill according to the mass ratio of Fe:Co:Cr:Ni:WC=1:1:1:1:1, the ball milling medium was Al2O3 ceramic balls, the ball-to-material mass ratio was 2:1, the rotation speed was 300r / min, the ball milling time was 60min, and then dried at 120°C for 2h to obtain FeCoCrNiWC high entropy metal ceramic powder;

[0057] 4. The eutectic high entropy alloy coating was prepared on the surface of the substrate by laser cladding process. 2.1 High entropy alloy powder is used as cladding powder, and the laser wavelength is controlled to be 1053nm, the laser power is 1500W, the scanning rate is 15mm / s, the overlap rate is 30%, the spot diameter is 3mm, the powder feeding rate is 0.15g / s, and the carrier gas flow rate is 20L / min. A eutectic high entropy alloy transition layer with a thickness of 0.5mm is formed on the surface of the substrate material;

[0058] 5. A eutectic high entropy alloy coating was prepared on the surface of the substrate material by laser cladding process. FeCoCrNiWC high entropy metal ceramic powder was used as cladding powder. The laser wavelength was controlled to be 1053nm, the laser power was 1500W, the scanning rate was 15mm / s, the overlap rate was 30%, the spot diameter was 3mm, the powder feeding rate was 0.15g / s, and the carrier gas flow rate was 20L / min. A high entropy metal ceramic layer with a thickness of 0.4mm was formed on the surface of the eutectic high entropy alloy transition layer to obtain a substrate material with a composite coating.

[0059] 6. Grinding and cleaning the base material with composite coating;

[0060] 7. Perform ultrasonic deep rolling treatment on the composite coating, using SHHS-GY ultrasonic rolling equipment, and control the ultrasonic deep rolling parameters as follows: ultrasonic vibration frequency 25kHz, ultrasonic deep rolling times 10 times, longitudinal feed speed 25mm / min, transverse feed step 0.2mm, and force 250N;

[0061] 8. Using electrochemical deposition technology, a high entropy alloy film is formed on the surface of the composite coating treated by ultrasonic deep rolling. The preparation process is as follows:

[0062] Prepare an electrolyte, wherein the electrolyte includes components such as soluble iron salt, cobalt salt, chromium salt, nickel salt, manganese salt, complexing agent, buffer, reducing agent and additional salt, wherein the soluble iron salt, cobalt salt, chromium salt, nickel salt and manganese salt are cobalt sulfate, chromium sulfate, ferrous sulfate, nickel sulfate and manganese sulfate respectively, the complexing agent is citric acid, the reducing agent includes sodium phosphite, the buffer includes boric acid, and the additional salt includes potassium chloride;

[0063] Weigh 60 g / L ferrous sulfate, 70 g / L cobalt sulfate, 55 g / L chromium sulfate, 80 g / L nickel sulfate, 3 g / L manganese sulfate, 100 g / L citric acid, 10 g / L trisodium citrate, 1 g / L sodium phosphite, 30 g / L boric acid, and 35 g / L potassium chloride respectively, heat 300 mL of deionized water and maintain the temperature at 50°C, then add citric acid and trisodium citrate, boric acid, potassium chloride, cobalt sulfate, chromium sulfate, ferrous sulfate, nickel sulfate, and manganese sulfate, stir until dissolved, and age for 5 hours to obtain an electrolyte;

[0064] Add 2 mol / L sulfuric acid solution to the electrolyte, adjust the electrolyte at a deposition potential of 1.5 V and a temperature of 50° C.;

[0065] A graphite rod was used as the anode and the treated composite coating was used as the cathode. Electroplating was carried out at a constant potential of -1.5 V for 10 minutes. A FeCoCrNiMn high entropy alloy film with controlled chemical composition was obtained on the composite coating treated by ultrasonic deep rolling.

[0066] The composite coating obtained in this embodiment has a top layer of FeCoCrNiMn high entropy alloy film, a middle layer of FeCoCrNiWC high entropy metal ceramic layer, and a transition layer of AlFeCoCrNi 2.1 The wear-resistant and tough multi-process coupled high-entropy alloy bionic structural coating of the eutectic high-entropy alloy layer. The cross-sectional hardness test of the wear-resistant and tough multi-process coupled high-entropy alloy bionic structural coating prepared in the embodiment was carried out using an HVST-1000 microhardness tester. The specific parameters were: load 300g, holding time 10s, spacing 20μm, and the test results were as follows: Figure 3 As shown; the tribological performance test was carried out using a friction and wear tester. The specific test parameters were: load 1000g, grinding ball Al2O3, frequency 5Hz, friction time 40min, friction radius 3mm, and the test results were as follows Figure 4 As shown by Figure 4 It can be seen that the average friction coefficient of the multi-process coupled high entropy alloy bionic structure coating is 0.572; the polarization test was carried out using a CHI600E electrochemical tester with specific parameters: potential -0.8~2V, and the test results are as follows Figure 5 As shown by Figure 5 It can be seen that the self-corrosion potential of the multi-process coupled high-entropy alloy bionic structure coating is -0.23166V, and the self-corrosion current density is 5.03269×10 -8 A / cm 2 .

Claims

1. A multi-process coupled high entropy alloy bionic structural coating with integrated wear resistance and toughness, characterized by The wear-resistant and tough multi-process coupled high-entropy alloy bionic structure coating is composed of a eutectic high-entropy alloy coating, a high-entropy metal ceramic layer and a high-entropy alloy film. x FeCoCrNi y Eutectic high entropy alloy powder is used as cladding powder, and a eutectic high entropy alloy coating is prepared on the surface of a substrate by a laser cladding process. Then, FeCoCrNiX high entropy metal ceramic powder is used as cladding powder, and a high entropy metal ceramic layer is formed on the eutectic high entropy alloy coating by a laser cladding process. The eutectic high entropy alloy coating and the high entropy metal ceramic layer form a composite coating. The composite coating is subjected to ultrasonic deep rolling treatment, and a high entropy alloy film is deposited on the composite coating by an electrochemical deposition process, thereby obtaining a multi-process coupled high entropy alloy bionic structure coating. The X in the FeCoCrNiX high entropy metal ceramic powder represents ceramic particles; the electrolyte in the electrochemical deposition process includes at least four metal salts of soluble aluminum salt, cobalt salt, chromium salt, iron salt, nickel salt, manganese salt, copper salt, and titanium salt, a complexing agent, and a reducing agent.

2. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 1 is characterized in that The preparation method of the multi-process coupled high entropy alloy bionic structure coating is implemented according to the following steps:

1. Grinding, polishing and cleaning the base material in sequence to obtain a pretreated base material; 2. Preparation of Al x FeCoCrNi y Eutectic high entropy alloy powder: Al powder, Fe powder, Co powder, Cr powder and Ni powder were mixed in a ball mill according to the atomic ratio of Al:Fe:Co:Cr:Ni=x:1:1:1:y to obtain Al x FeCoCrNi y Eutectic high entropy alloy powder; 3. Preparation of FeCoCrNiX high entropy metal ceramic powder, X represents ceramic particles: Fe powder, Co powder, Cr powder, Ni powder and ceramic particles X are mixed in a ball mill according to a mass ratio of Fe:Co:Cr:Ni:X=1:1:1:1:1 to obtain FeCoCrNiX high entropy metal ceramic powder; 4. Al x FeCoCrNi y Eutectic high entropy alloy powder is used as cladding powder, and a eutectic high entropy alloy coating is prepared on the surface of the substrate by laser cladding process; 5. Using FeCoCrNiX high entropy metal ceramic powder as cladding powder, a laser cladding process is used to in-situ clad the eutectic high entropy alloy coating to form a high entropy metal ceramic layer, thereby obtaining a substrate material with a composite coating; 6. Grind and clean the base material with the composite coating in turn; 7. Perform ultrasonic deep rolling treatment on the composite coating on the base material; 8. Using an electrochemical deposition process, a high entropy alloy film is deposited on the composite coating to obtain a multi-process coupled high entropy alloy bionic structure coating; The electrolyte in the electrochemical deposition process in step eight includes at least four metal salts of soluble aluminum salt, cobalt salt, chromium salt, iron salt, nickel salt, manganese salt, copper salt and titanium salt, a complexing agent and a reducing agent.

3. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that Step 2 Al x FeCoCrNi y The preparation method of eutectic high entropy alloy powder is as follows: According to the atomic ratio of Al:Fe:Co:Cr:Ni=x:1:1:1:y, the metal powders were mixed in a ball mill. The ball-to-material mass ratio was controlled to be 2:

1. The rotation speed was 300-350r / min. The ball milling time was 40-60min. Al was obtained after drying. x FeCoCrNi y Eutectic high entropy alloy powder; The Al x FeCoCrNi y In eutectic high entropy alloys, x is 0.7 to 1 and y is 1 to 2.

1.

4. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that The ceramic particles in step three are WC, TiC, Cr3C2 or SiC.

5. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that In the laser cladding process in step 4, the laser wavelength is controlled to be 1053 nm, the laser power is 1500-2000 W, and the scanning rate is 10-20 mm / s.

6. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that In the laser cladding process in step 5, the laser wavelength is controlled to be 1053 nm, the laser power is 1500-2500 w, and the scanning rate is 8-15 mm / s.

7. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that The process parameters for controlling the ultrasonic deep rolling treatment in step seven are: ultrasonic vibration frequency of 20-30kHz, ultrasonic deep rolling times of 5-15 times, longitudinal feed speed of 20-30mm / min, transverse feed step of 0.1-0.3mm, and action force of 250-300N.

8. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that In step eight, the complexing agent in the electrolyte is citric acid or trisodium citrate, and the reducing agent is sodium phosphite or ascorbic acid.

9. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2 is characterized in that In the electrochemical deposition process in step eight, a graphite rod is used as an anode, a substrate material with a composite coating is used as a cathode, an electrolyte temperature is 30 to 80° C., and a constant potential of 0.5 to 3 V is used for electroplating deposition for 5 to 10 minutes.

10. The method for preparing the wear-resistant and tough integrated multi-process coupled high-entropy alloy bionic structural coating according to claim 2, characterized in that The thickness of the eutectic high entropy alloy coating is 0.3-0.6 mm, and the thickness of the high entropy metal ceramic layer is 0.3-0.5 mm.

Citation Information

Cited By

  • High-temperature wear-resistant high-entropy alloy-based composite coating and preparation method thereof

    CN120796813A

  • Eutectic high-entropy alloy wear-resistant coating with micro-nano multistage heterostructure and preparation method and application thereof

    CN122406221A